A CROSS-SECTIONAL STUDY ON SELF-MEDICATION PRACTICES, PERCEPTION, AND ATTITUDES OF UNDERGRADUATE MEDICAL STUDENTS AT A GOVERNMENT TERTIARY CARE TEACHING HOSPITAL IN EASTERN INDIA - BANERJEE, KUSHAL; BANERJEE, MANASI BASU; GHOSH, ABHISHEK (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Self-medication (SM) is common in India. It is of greater significance when practiced by medical students as they going to be medical practitioners in the future. This study was conducted to assess the pattern of SM practices, perceptions, and attitudes among students pursuing 2nd-year professional MBBS in a tertiary medical college in the year 2019. Methods: This study was a cross-sectional one based on a questionnaire. It was conducted among the 2nd-year undergraduate (MBBS) medical students in a tertiary care medical college in West Bengal, India. Results: Out of 199 students approached, 198 consented to the study and filled in the supplied study questionnaire. Thirteen incomplete questionnaires were excluded and the remaining 185 were analyzed. It was found that 81.6% (151/185) respondents practiced SM. The most common ailments for seeking SM were fever 66.2% (100/151), followed by cough cold, and sore throat 55.0% (84/151), diarrhea/nausea, and vomiting 40.4% (61/151). The most common drug used for SM was paracetamol 73.51% (111/151), followed by H1 antihistaminics and proton pump inhibitors. A small percentage of students used topical preparations of steroids, analgesics, antibiotics, and antifungals as well. Among the common reasons for seeking SM, 72.2% (109/151) felt that their illness was mild and 57% (86/151) preferred it as they had prior experience. Conclusion: Our study showed that SM is commonly practiced among the students of this institution. Therefore, medical teachers need to try even more to generate adequate awareness among the students about inherent risks of SM.